Hydrogenation catalysts, processes for their preparation and use
Patent Information
- Application Number
- CN202510570131.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
当前,普通氧化铝酸性较为单一、负载金属时与活性组分间的作用太强,导致深度加氢的目的还不能很好的实现
[0087]本发明提供了一种加氢催化剂的制备方法,首先,采用自组装法,主要通过控制醇/铝摩尔比、醇/模板剂摩尔比以及模板剂的引入方式,同时在自组装的过程中引入金属钛以及双功能结构导向剂,结合水热处理,进一步优化介孔氧化铝的比表面积、孔结构和表面酸分布。以上述改性介孔氧化铝材料为基础,将其与具备大孔的高温型活性炭以及部分主活性金属(第VIB族金属)混合成型,然后采用“内水相/油相/外水相”型多相浸渍液负载剩余的活性金属,通过各步骤综合协调,从而显著提高催化剂脱金属活性性能以及长周期运转性能。
Smart Images

Figure BDA0005386953530000151 
Figure BDA0005386953530000152 
Figure BDA0005386953530000153
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst preparation, specifically relating to a hydrogenation catalyst, its preparation method, and its application. Background Technology
[0002] With the increasing trend of heavier and lower-quality crude oil worldwide, heavy oil hydrotreating technology plays an increasingly important role in the efficient utilization and lightening of crude oil. Alumina, as the main carrier of hydrotreating catalysts, possesses characteristics such as a large specific surface area, excellent pore structure, a certain acid strength distribution, and high hydrothermal and thermal stability, playing a crucial role in the hydrotreating process. Currently, ordinary alumina has relatively simple acidity, and the interaction between loaded metals and active components is too strong, preventing the full realization of deep hydrotreating goals. Especially in the hydrotreating of heavy oil, the small pore size of ordinary alumina restricts the diffusion of large molecules during the reaction, making the catalyst more prone to deactivation, and the utilization rate of active metals needs further improvement.
[0003] CN103539173A discloses a method for preparing a highly thermally stable ordered mesoporous alumina material. This material maintains good pore order after calcination at 1000℃ for 1 hour. It uses inorganic aluminum sources such as aluminum nitrate and aluminum chloride as raw materials, P123 as a template agent, and organic carboxylic acids as surface protectants in ethanol and aqueous solutions. The ordered mesoporous alumina material is synthesized through solvent evaporation-induced self-assembly. The pore size of this material is 4.0–10.0 nm, and the specific surface area is 200–400 m². 2 / g, pore volume 0.3~1.0cm³ 3 / g.
[0004] Currently, there are many ways to synthesize alumina, but how to prepare alumina-based support materials with better overall performance, and on the basis of the above, prepare hydrogenation catalysts with excellent performance, is an important research direction. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a hydrogenation catalyst, its preparation method, and its application. The hydrogenation catalyst of this invention, used in the hydrodemetallization reaction of residual oil, exhibits strong hydrogenation activity, significantly improving its reaction performance and ensuring long-term stable operation of the hydrogenation unit.
[0006] The first aspect of this invention provides a method for preparing a hydrogenation catalyst, comprising the following steps:
[0007] (1) Titanium-modified mesoporous alumina, activated carbon, a first active metal source and molding aid are mixed and shaped, dried and calcined to obtain a composite carrier containing the first active metal.
[0008] (2) The second active metal is loaded onto the composite support obtained in step (1), dried, and calcined to obtain the catalyst.
[0009] Further, in step (1), the activated carbon is a high-temperature activated carbon, with a minimum heat resistance temperature of not less than 700℃, preferably 750~900℃. The activated carbon has a pore volume of 1.0~1.8mL / g, and the pore volume with a pore size of 50.0~300.0nm accounts for 15%~45% of the total pore volume.
[0010] Further, in step (1), the molding aid is one or more of guar gum powder, methylcellulose, etc. The molding method can be at least one of extrusion, tableting, and ball rolling. The shaped product can be clover-shaped, four-leaf clover-shaped, butterfly-shaped, cylindrical, spherical, or strip-shaped, etc.
[0011] Further, in step (1), the mass of the molding aid added is 1.0% to 8.0% of the total mass of titanium-modified mesoporous alumina and activated carbon.
[0012] Further, in step (1), the first active metal is one or more group VIB metals, preferably Mo and / or W; further, the molybdenum source is selected from at least one of ammonium heptamolybdate, ammonium tetramolybdate, and molybdenum oxide; the tungsten source is preferably ammonium metatungstate. The mass (in oxides) of the first active metal source is 10% to 25% of the total mass of titanium-modified mesoporous alumina and activated carbon.
[0013] Further, in step (1), the drying temperature is 120–200°C, and the drying time is 4–10 h. The calcination temperature is 500–650°C, and the calcination time is 3–8 h.
[0014] Further, in step (2), the preferred loading method is saturated impregnation. After impregnation, the catalyst is obtained by conventional filtration, washing, drying, and calcination. The drying temperature is 120–200°C, and the drying time is 4–10 h. The calcination temperature is 500–650°C, and the calcination time is 3–8 h.
[0015] Further, in step (2), the second active metal includes Group VIB metals and Group VIII metals. The second active metal is introduced into the catalyst through an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal.
[0016] Furthermore, the impregnation solution containing the second active metal comprises an inner aqueous phase, an oil phase coating the inner aqueous phase, and an outer aqueous phase. The inner aqueous phase comprises a Group VIB metal source, a co-emulsifier, a water-soluble polymer, water, and an optional phosphorus source. The outer aqueous phase comprises a Group VIII metal source, a hydrophilic agent, and water. The oil phase comprises a surfactant and oil.
[0017] Further, the mass ratio of surfactant to oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0, more preferably 1.0:4.0 to 10.0, for example 1.0:4.0, 1.0:4.5, 1.0:5.0, 1.0:5.5, 1.0:6.0, 1.0:6.5, 1.0:7.0, 1.0:7.5, 1.0:8.0, 1.0:8.5, 1.0:9.0, 1.0:9.5, 1.0:10.0, etc., and any value within the range formed by any two of these values.
[0018] Furthermore, the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0, for example 0.5:1.0, 0.7:1.0, 0.9:1.0, 1.0:1.0, 1.5:1.0, 2.0:1.0, 3.0:1.0, 4.0:1.0, 5.0:1.0, 6.0:1.0, 7.0:1.0, 8.0:1.0, 9.0:1.0, etc., and any value within the range formed by any two of these values.
[0019] Furthermore, the mass ratio of the "internal aqueous phase / oil phase" to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.0, for example 0.5:1.0, 0.7:1.0, 0.9:1.0, 1.0:1.0, 1.5:1.0, 2.0:1.0, 3.0:1.0, 4.0:1.0, 5.0:1.0, 6.0:1.0, 7.0:1.0, 8.0:1.0, etc., and any value within the range formed by any two of these values.
[0020] Furthermore, the water-soluble polymer is one or more of polyvinyl alcohol (molecular weight 170,000 to 220,000), carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate (molecular weight less than 10,000).
[0021] Furthermore, in the internal aqueous phase, the mass concentration of the water-soluble polymer is 4.0% to 14.0%.
[0022] Furthermore, in the inner aqueous phase, the concentration of Group VIB metals as oxides is 8-80 g / 100 mL, preferably 10-60 g / 100 mL; in the outer aqueous phase, the concentration of Group VIII metals as oxides is 2-50 g / 100 mL, preferably 5-30 g / 100 mL.
[0023] Further, the Group VIB metal is Mo and / or W, and the Group VIII metal is Ni and / or Co. The Group VIB metal source is one or more of ammonium tetramolybdate, ammonium heptamolybdate, ammonium metatungstate, and molybdenum oxide, and the Group VIII metal source is one or more of basic nickel nitrate, cobalt nitrate, etc.
[0024] Furthermore, in the internal aqueous phase, the additive is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus, and the phosphorus source is one or more of phosphoric acid, ammonium hydrogen phosphate, and ammonium dihydrogen phosphate. In the internal aqueous phase, the concentration of the additive, calculated as an oxide, is 0–12.0 g / 100 mL, preferably 0.5–12.0 g / 100 mL.
[0025] Further, the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, and glycerin. The mass concentration of the co-emulsifier in the internal aqueous phase is 0.5% to 5.0%.
[0026] Further, the hydrophilic agent is one or more selected from polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide. In the external aqueous phase, the mass concentration of the hydrophilic agent is 5.0% to 15.0%.
[0027] Furthermore, the surfactant is selected from glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol (structure R-(OCC)). x -OH, where R is a straight-chain alkyl group with 12 to 15 carbon atoms, and x is 2 to 11, etc.
[0028] Furthermore, the oil is selected from at least one of silicone oil and vegetable oil, the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
[0029] Further, in step (2), the method for preparing the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal includes:
[0030] (a) The surfactant and oil are mixed and heated to obtain the oil phase;
[0031] (b) Mix the co-emulsifier, the Group VIB metal source, water and optional auxiliary source, and heat to obtain a clear solution;
[0032] (c) Add a water-soluble polymer to the clear solution obtained in step (b) to obtain an internal aqueous phase;
[0033] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a) while the oil phase remains liquid during the dropwise addition. Simultaneously, stirring and shearing are performed to homogenize the mixture, resulting in an "aqueous phase / oil phase" emulsion.
[0034] (e) Mixing a Group VIII metal source with water containing a hydrophilic agent to obtain an external aqueous phase;
[0035] (f) The “inner aqueous phase / oil phase” type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (e) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0036] Further, in step (a), the surfactant is selected from glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol (structure R-(OCC)). x -OH, where R is a straight-chain alkyl group with 12 to 15 carbon atoms, and x is 2 to 11, etc., or one or more of these. The oil may be at least one of silicone oil and vegetable oil, wherein the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
[0037] Furthermore, in step (a), the heating is carried out to a temperature of 45–85°C to make the oil phase appear as a uniform liquid.
[0038] Further, in step (a), the mass ratio of the added surfactant to the mass of the oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0.
[0039] Further, in step (a), the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, polyvinyl alcohol, and glycerin.
[0040] Further, in step (a), the amount of the co-emulsifier is 0.5% to 5.0% of the mass of the internal aqueous phase obtained in step (c).
[0041] Further, in step (b), the Group VIB metal is Mo and / or W, and the Group VIB metal source can be one or more of molybdenum oxide, ammonium tetramolybdate, ammonium heptamolybdate, ammonium metatungstate, etc. The additive is selected from at least one of fluorine, phosphorus, silicon, or boron, preferably phosphorus, and the phosphorus source can be one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, etc.
[0042] Further, in step (b), the water is distilled water or deionized water, and the conductivity of the water should be less than 10.0 mS.
[0043] Further, in step (b), the heating is carried out to a temperature of 90-120°C to ensure that the substances added in step (b) are mixed evenly until a clear solution is obtained.
[0044] Further, in step (c), the concentration of Group VIB metals as oxides in the internal aqueous phase is 8-80 g / 100 mL, preferably 10-60 g / 100 mL, and the concentration of additives as oxides is 0-12.0 g / 100 mL, preferably 0.5-12.0 g / 100 mL.
[0045] Further, in step (c), the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate.
[0046] Further, in step (d), the mass concentration of the water-soluble polymer in the aqueous phase obtained in step (d) is 4.0% to 14.0%.
[0047] Furthermore, in step (d), the oil phase is kept in a liquid state at a temperature of 45–85°C, and the stirring rate is 400–800 r / min.
[0048] Further, in step (d), the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0.
[0049] Further, in step (d), the stirring-shear homogenization process is carried out at a stirring speed of 10,000 to 18,000 rpm, a shear homogenization time of 3 to 8 min, and a temperature of 50 to 85°C.
[0050] Further, in step (e), the Group VIII metal is Ni and / or Co; the Group VIII metal source is one or more of basic nickel carbonate, cobalt nitrate, etc.
[0051] Further, in step (e), the hydrophilic agent is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide.
[0052] Further, in step (e), the water is distilled water or deionized water, and the conductivity of the water should be less than 10.0 mS.
[0053] Further, in step (e), the mass concentration of the hydrophilic agent in the external aqueous phase is 5.0% to 15.0%.
[0054] Further, in step (e), the concentration of Group VIII metals in the external aqueous phase, calculated as oxides, is 2 to 50 g / 100 mL, preferably 5 to 30 g / 100 mL.
[0055] Further, in step (e), the mass ratio of the "internal aqueous phase / oil phase" emulsion to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.0.
[0056] Furthermore, the specific surface area of the titanium-modified mesoporous alumina is 150–450 m². 2 / g, preferably 210-320m 2 / g, with a mesopore size of 6.0–25.0 nm, preferably 7–17 nm, and a pore volume of 0.5–1.5 mL / g, preferably 0.8–1.2 mL / g.
[0057] Furthermore, in the titanium-modified mesoporous alumina, the molar ratio of titanium to aluminum is 0.2 to 1.0.
[0058] Furthermore, in the titanium-modified alumina, the content of medium-strong acids accounts for 59% to 65% of the total acid content, preferably 62% to 65%. The total acid content refers to the sum of the amounts of weak acids, medium-strong acids, and strong acids. The total acid content is 0.215 to 0.275 mmol / g, preferably 0.215 to 0.240 mmol / g.
[0059] Further, in step (1), the method for preparing the titanium-modified mesoporous alumina includes the following steps:
[0060] (I) Mix aluminum source, acid and alcohol, and perform pre-hydrolysis to obtain solution A;
[0061] (II) Mix the template agent and alcohol to obtain solution B;
[0062] (III) Mix solution A, solution B and the solution containing titanium source to obtain solution D;
[0063] (IV) After adding the bifunctional structure directing agent dropwise to solution D, perform hydrothermal treatment, dry, and calcine to obtain the titanium-modified mesoporous alumina.
[0064] Further, in step (I), the pre-hydrolysis is carried out under stirring conditions, and the stirring rate is not particularly limited. The temperature of the pre-hydrolysis is 20–60°C, and the pre-hydrolysis time is 1–12 hours. Further, the aluminum source is one or more of aluminum sources such as aluminum nitrate, aluminum chloride, and aluminum isopropoxide. The acid is an inorganic acid, preferably one or more of sulfuric acid, nitric acid, and hydrochloric acid. The alcohol is a low-carbon alcohol, preferably one or more of ethanol, propanol, and butanol.
[0065] Further, in step (I), the alcohol / aluminum molar ratio is 10.0 to 80.0, preferably 15.0 to 55.0.
[0066] Further, in step (I), the acid / aluminum molar ratio is 1.0 to 10.0, preferably 1.0 to 7.0.
[0067] Further, preferably, in step (I), the aluminum source, acid, and alcohol are first mixed and pre-hydrolyzed to obtain a precursor solution. Then, an ionic emulsifier is added dropwise to the precursor solution to obtain solution A. The amount of the ionic emulsifier added is related to the amount of the precursor solution by 5–20 g / 100 mL.
[0068] Furthermore, the ionic emulsifier is one or more of anionic emulsifiers such as sodium dodecyl sulfate and fatty polyoxyethylene ether sulfate salt (chemical structure formula RO(CH2CH2O)n-SO3Na (n=1~15, R is a fatty alkyl group of C10~C22)).
[0069] Furthermore, the molar ratio of the sum of the aluminum source in step (I) and the titanium source in step (III) to the molar ratio of the template agent in step (II) is 50 to 90.
[0070] Further, in step (II), the template agent is at least one of P123, SDBS, and AOT, preferably P123. Mixing is carried out under stirring conditions, with no particular limitation on the stirring rate. The stirring temperature is 20–65°C, and the stirring time is 2–6 hours.
[0071] Further, in step (III), the titanium source-containing solution comprises a titanium source, an acid, and an alcohol, wherein the alcohol is preferably ethanol, and the acid is preferably nitric acid; the titanium source is selected from at least one of titanium isopropoxide, tetrabutyl titanate, methyl titanate, and tetraethyl titanate. In the titanium source-containing solution, the volume ratio of alcohol to acid is 4–12. Further, the titanium source, alcohol, and acid are mixed to obtain a titanium source-containing solution, denoted as solution T. Preferably, in the titanium source-containing solution, the ratio of the mass of titanium element to the sum of the volumes of acid and alcohol is 0.02–0.15 g / mL, more preferably 0.05–0.11 g / mL.
[0072] Further, preferably, in step (III), solution A is first added dropwise to solution B to obtain solution C, and then solution T is added dropwise to solution C to obtain solution D. Preferably, the molar ratio of the titanium source to the aluminum source in step (I) is 0.2 to 1.0.
[0073] Furthermore, in step (III), mixing is carried out under stirring conditions, with no particular limitation on the stirring rate. The stirring temperature is 20–65°C, and the stirring time is 2–6 hours.
[0074] Further, in step (IV), the bifunctional structural directing agent is polyethylene glycol-distearate phosphatidylethanolamine (molecular weight 500-5000). Further, the ratio of the molar amount of the bifunctional structural directing agent to the sum of the molar amounts of the bifunctional structural directing agent and the aluminum source in solution A is 0.05-0.35.
[0075] Further, in step (IV), the conditions for the hydrothermal treatment are: temperature 140–240°C, preferably 150–235°C, and time 3–10 h, preferably 4–8 h.
[0076] Further, in step (IV), after the hydrothermal treatment, the alumina is first cooled to room temperature (20–30°C), then dried and calcined to obtain mesoporous alumina. The drying temperature is 120–200°C, and the drying time is 4–10 hours. The calcination temperature is 500–650°C, and the calcination time is 3–8 hours.
[0077] A second aspect of the present invention provides a hydrogenation catalyst prepared by any of the methods described in the first aspect.
[0078] Furthermore, the hydrogenation catalyst comprises a composite support containing a first active metal and a second active metal, wherein the composite support containing the first active metal comprises titanium-modified mesoporous alumina, activated carbon, and the first active metal.
[0079] Further, the first active metal is selected from at least one of Group VIB metals, preferably Mo and / or W; the second active metal includes at least one of Group VIII metals and at least one of Group VIB metals, wherein the Group VIII metal is preferably Ni and / or Co, and the Group VIB metal is preferably Mo and / or W.
[0080] Furthermore, in the composite carrier, the mass ratio of titanium-modified mesoporous alumina to activated carbon is 2.5 to 6.5.
[0081] Furthermore, in the catalyst, based on the mass of the catalyst, the content of Group VIB metal oxide is 6% to 20%, preferably 10% to 18%, and the content of Group VIII metal oxide is 1% to 10%, preferably 2% to 8%; wherein the mass ratio of Group VIB metal oxide in the first active metal to Group VIB metal oxide in the second active metal is 0.5 to 6.0.
[0082] Furthermore, the catalyst also includes an additive, the content of which, based on the mass of the catalyst, is 0-8% (calculated as oxide), preferably 1-6%.
[0083] Furthermore, in the catalyst, the mesopore volume with a pore size of 6.0–25.0 nm accounts for 20.0%–45.0% of the total pore volume, preferably 30.0%–41.0%, and the macropore volume with a pore size of 50.0–300.0 nm accounts for 20.0%–35.0% of the total pore volume, preferably 23.5%–35.0%.
[0084] Further, in the catalyst, the molar ratio of the amount of Brønsted acid to the sum of the amounts of Brønsted acid and Lewis acid is 0.310–0.390, preferably 0.350–0.388. In the catalyst, the amount of Brønsted acid is 11.0–17.9 μmol / g, preferably 15.4–17.7 μmol / g.
[0085] The third aspect of the present invention provides the application of the above-mentioned catalyst in the hydrodemetallization of residue oil.
[0086] Compared with the prior art, the present invention has the following beneficial effects:
[0087] This invention provides a method for preparing a hydrogenation catalyst. First, a self-assembly method is employed, primarily by controlling the alcohol / aluminum molar ratio, the alcohol / template molar ratio, and the introduction method of the template agent. Simultaneously, titanium metal and a bifunctional directing agent are introduced during the self-assembly process. Combined with hydrothermal treatment, the specific surface area, pore structure, and surface acid distribution of mesoporous alumina are further optimized. Based on the aforementioned modified mesoporous alumina material, it is mixed with high-temperature activated carbon possessing macropores and some of the main active metals (Group VIB metals) to form a composite. Then, the remaining active metals are loaded using an "internal aqueous phase / oil phase / external aqueous phase" multiphase impregnation solution. Through the comprehensive coordination of these steps, the catalyst's demetallization activity and long-term operating performance are significantly improved. Detailed Implementation
[0088] The technical solutions and effects of the present invention will be further illustrated below with reference to the embodiments, but the invention is not limited to the following embodiments.
[0089] In this invention, the specific surface area and pore volume of the samples were characterized using a Micromeritics ASAP2420 fully automated specific surface area analyzer from Micromeritics, Inc., USA. The treated samples were loaded into the fully automated specific surface area analyzer for property testing using a low-temperature nitrogen isothermal adsorption method. The specific surface area of the samples was calculated using the BET method.
[0090] In this invention, the determination of L-acid or Brønsted acid is performed using infrared spectroscopy. The instrument used is a Nicot Fourier Transform Infrared Spectrometer-6700 (USA). The determination method is as follows: The sample to be measured is ground and pressed into a thin sheet with a thickness of approximately 0.1 mm, which is then placed in an infrared cell. The in-situ infrared cell is heated from room temperature to 350 °C over a programmed temperature range of 20 min and held for 120 min, then cooled to 200 °C over a 10 min period. The in-situ cell is then evacuated to a vacuum of 0.01 Pa. The sample is scanned as the background spectrum, and pyridine vapor is used as a probe molecule to scan the sample at 200 °C. The total amount of total acid, Brønsted acid, and L-acid can then be obtained. The units for the amounts of Brønsted acid and L-acid are μmol / g.
[0091] In this invention, the acid content of moderately strong acids was determined using the NH3-TPD method. The instrument used was an Auto-Chem II 2920 chemisorption analyzer from Micron Instruments. Ammonia was used as the adsorption / desorption medium, and helium as the carrier gas. Programmed temperature desorption and chromatographic analysis were employed to obtain the acid content in different desorption temperature ranges. The acid content of weak acids corresponds to an ammonia desorption temperature below 200℃, the acid content of moderately strong acids corresponds to an ammonia desorption temperature of 200℃–400℃, and the acid content of strong acids corresponds to an ammonia desorption temperature above 400℃. The unit of acid content is mmol / g, which represents the amount of ammonia adsorbed per gram of molecular sieve. The sum of the acid content of weak, moderately strong, and strong acids is the total acid content.
[0092] In various embodiments of the present invention, the molecular weight of the bifunctional structure-directing agent polyethylene glycol-distearatephosphatidylethanolamine is 872.14.
[0093] In each example of the present invention, the room temperature is 25°C.
[0094] Example 1
[0095] Preparation of titanium-modified mesoporous alumina in this example:
[0096] (I) Add 50g of aluminum isopropoxide and 45mL of nitric acid to 420mL of ethanol and stir at room temperature for 4h to perform pre-hydrolysis to obtain a precursor solution; add 35g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0097] (II) Add 51g of template agent P123 to 280mL of ethanol, stir at room temperature for 6h to obtain solution B;
[0098] (III) Add solution A dropwise to B to obtain solution C; weigh 17g of titanium isopropoxide and dissolve it in 56mL of ethanol and 8mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0099] (IV) Add 46g of the bifunctional structure-directing agent polyethylene glycol-distearatephosphatidylethanolamine dropwise to solution D and perform hydrothermal treatment at 150℃ for 5h. After hydrothermal treatment, cool to room temperature to obtain solution E. Place solution E in an oven at 180℃ and allow the solvent to evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain titanium-modified mesoporous alumina.
[0100] This example illustrates the preparation of an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal:
[0101] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:7.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 5:15:8:18:85. The mass ratio of oil phase to internal aqueous phase is 1.0:0.6. The mass ratio of nickel source (calculated as nickel oxide):hydrophilic agent:water is 18:32:325. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 0.7:1.0.
[0102] (a) Add the surfactant glyceryl monostearate to the silicone oil, heat to 80°C, and wait for the silicone oil to melt to obtain the oil phase;
[0103] (b) Add the co-emulsifier polyethylene glycol-8000, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 500 r / min. When the temperature is raised to 120°C, the temperature is maintained for 3 hours. The stirring speed is kept constant until a clear solution is obtained.
[0104] (c) Add water-soluble polymer polyvinyl alcohol to the clear solution obtained in step (b) to obtain an inner aqueous phase;
[0105] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the dropwise addition, the temperature of the oil phase is maintained at 80°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 4 min, and the temperature during the shear homogenization process is 75°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0106] (e) Add the hydrophilic agent to the water, and then add basic nickel carbonate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0107] (f) The “inner aqueous phase / oil phase” type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (f) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0108] Preparation of the hydrogenation catalyst in this example:
[0109] (1) 268g of titanium-modified mesoporous alumina, 84g of high-temperature activated carbon (heat resistance temperature of 900℃, pore volume of 1.7mL / g, and pore volume of 50~300nm accounting for 40% of the total pore volume), 7.5g of guar gum powder, 73g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0110] (2) Prepare an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, saturate the composite carrier obtained in step (1), and after drying at 120℃ for 6 hours and calcining at 550℃ for 4 hours, obtain the residue oil demetallization catalyst.
[0111] Example 2
[0112] Preparation of titanium-modified mesoporous alumina in this example:
[0113] (I) Add 88g of aluminum isopropoxide and 56mL of nitric acid to 380mL of ethanol and stir at room temperature for 4h to perform pre-hydrolysis to obtain a precursor solution; add 45g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0114] (II) Add 62g of template agent P123 to 254mL of ethanol, stir at room temperature for 6h to obtain solution B;
[0115] (III) Add solution A dropwise to B to obtain solution C; weigh 30 g of titanium isopropoxide and dissolve it in 89 mL of ethanol and 10 mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0116] (IV) Add 35g of the bifunctional structure-directing agent polyethylene glycol-distearatephosphatidylethanolamine dropwise to solution D and perform hydrothermal treatment at 165℃ for 4h. After hydrothermal treatment, cool to room temperature to obtain solution E. Place solution E in an oven at 180℃ and allow the solvent to evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain titanium-modified mesoporous alumina.
[0117] This example illustrates the preparation of an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal:
[0118] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:4.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 12:35:8:18:331. The mass ratio of oil phase to internal aqueous phase is 1.0:4.0. The mass ratio of nickel source (calculated as nickel oxide):hydrophilic agent:water is 24:32:276. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 1.5:1.0.
[0119] (a) Add the surfactant glyceryl monostearate to the silicone oil, heat to 80°C, and wait for the silicone oil to melt to obtain the oil phase;
[0120] (b) Add the co-emulsifier polyethylene glycol-8000, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 500 r / min. When the temperature is raised to 120°C, the temperature is maintained for 3 hours. The stirring speed is kept constant until a clear solution is obtained.
[0121] (c) Add water-soluble polymer polyvinyl alcohol to the clear solution obtained in step (b) to obtain an inner aqueous phase;
[0122] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the dropwise addition, the temperature of the oil phase is maintained at 80°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 4 min, and the temperature during the shear homogenization process is 75°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0123] (e) Add the hydrophilic agent to the water, and then add basic nickel carbonate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0124] (f) The “inner aqueous phase / oil phase” type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (f) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0125] Preparation of the hydrogenation catalyst in this example:
[0126] (1) 358g of titanium-modified mesoporous alumina, 98g of high-temperature activated carbon (heat resistance temperature of 850℃, pore volume of 1.5mL / g, and pore size of 50~300nm accounting for 35% of the total pore volume), 8.0g of guar gum powder, 73g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0127] (2) Prepare an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, saturate the composite carrier obtained in step (1), and after drying at 120℃ for 6 hours and calcining at 550℃ for 4 hours, obtain the residue oil demetallization catalyst.
[0128] Example 3
[0129] This example of titanium-modified mesoporous alumina is the same as in Example 1.
[0130] This example illustrates the preparation of an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal:
[0131] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the surfactant to silicone oil mass ratio is 1.0:6.6. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 5:35:8:18:264. The mass ratio of oil phase to internal aqueous phase is 1.0:2.0. The mass ratio of nickel source (calculated as nickel oxide):hydrophilic agent:water is 18:25:132. The mass ratio of "internal aqueous phase / oil phase" type emulsion to external aqueous phase is 3.0:1.0.
[0132] (a) Add the surfactant glyceryl monostearate to the silicone oil, heat to 80°C, and wait for the silicone oil to melt to obtain the oil phase;
[0133] (b) Add the co-emulsifier polyethylene glycol-8000, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 500 r / min. When the temperature is raised to 120°C, the temperature is maintained for 3 hours. The stirring speed is kept constant until a clear solution is obtained.
[0134] (c) Add water-soluble polymer polyvinyl alcohol to the clear solution obtained in step (b) to obtain an inner aqueous phase;
[0135] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the dropwise addition, the temperature of the oil phase is maintained at 80°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 4 min, and the temperature during the shear homogenization process is 75°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0136] (e) Add the hydrophilic agent to the water, and then add basic nickel carbonate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0137] (f) The “inner aqueous phase / oil phase” type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (f) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0138] Preparation of the hydrogenation catalyst in this example:
[0139] (1) 268g of titanium-modified mesoporous alumina, 84g of high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.4mL / g, and pore size of 50~300nm accounting for 35% of the total pore volume), 9.0g of guar gum powder, 49g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0140] (2) Prepare an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, saturate the composite carrier obtained in step (1), and after drying at 120℃ for 6 hours and calcining at 550℃ for 4 hours, obtain the residue oil demetallization catalyst.
[0141] Example 4
[0142] Preparation of titanium-modified mesoporous alumina in this example:
[0143] (I) Add 55g of aluminum isopropoxide and 78mL of nitric acid to 390mL of ethanol and stir at room temperature for 4h to perform pre-hydrolysis to obtain a precursor solution; add 25g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0144] (II) Add 36g of template agent P123 to 190mL of ethanol, stir at room temperature for 6h to obtain solution B;
[0145] (III) Add solution A dropwise to B to obtain solution C; weigh 17g of titanium isopropoxide and dissolve it in 86mL of ethanol and 10mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0146] (IV) Add 54g of the bifunctional structure-directing agent polyethylene glycol-distearatephosphatidylethanolamine dropwise to solution D and perform hydrothermal treatment at 150℃ for 5h. After hydrothermal treatment, cool to room temperature to obtain solution E. Place solution E in an oven at 180℃ and allow the solvent to evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain titanium-modified mesoporous alumina.
[0147] The "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0148] The hydrogenation catalyst in this example was prepared according to the method in Example 1.
[0149] Example 5
[0150] Preparation of titanium-modified mesoporous alumina in this example:
[0151] (I) Add 69g of aluminum isopropoxide and 86mL of nitric acid to 312mL of ethanol and stir at room temperature for 4h to perform pre-hydrolysis to obtain a precursor solution; add 32g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain solution A.
[0152] (II) Add 42g of template agent P123 to 280mL of ethanol, stir at room temperature for 6h to obtain solution B;
[0153] (III) Add solution A dropwise to B to obtain solution C; weigh 10 g of titanium isopropoxide and dissolve it in 96 mL of ethanol and 10 mL of nitric acid to obtain solution T; add solution T dropwise to solution C to obtain solution D;
[0154] (IV) Add 56g of the bifunctional structure-directing agent polyethylene glycol-distearatephosphatidylethanolamine dropwise to solution D and perform hydrothermal treatment at 150℃ for 5h. After hydrothermal treatment, cool to room temperature to obtain solution E. Place solution E in an oven at 180℃ and allow the solvent to evaporate automatically until the sample is dry. Then calcine it in a muffle furnace at 650℃ for 3h to obtain titanium-modified mesoporous alumina.
[0155] The "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0156] Preparation of the hydrogenation catalyst in this example:
[0157] (1) 280g of titanium-modified mesoporous alumina, 68g of high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.2mL / g, and pore volume of 50~300nm accounting for 20% of the total pore volume), 8g of guar gum powder, 71g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0158] (2) Prepare an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, saturate the composite carrier obtained in step (1), and after drying at 120℃ for 6 hours and calcining at 550℃ for 4 hours, obtain the residue oil demetallization catalyst.
[0159] Comparative Example 1
[0160] In this example, mesoporous alumina was prepared according to the method described in the literature ("Preparation and Properties of Templated Mesoporous Alumina Materials." Journal of Dalian Railway Institute 27.1 (2006): 71-75).
[0161] Weigh 50g of aluminum isopropoxide and dissolve it in 420mL of ethanol. Add 45mL of nitric acid to form a sol. Stir the solution in an 80℃ water bath for 1h. When the solution cools to room temperature, weigh 51g of P123 and dissolve it in the solution. Stir for 1h. Then transfer the solution to a stainless steel autoclave lined with polytetrafluoroethylene for hydrothermal reaction at a filling degree of 70%, a hydrothermal reaction temperature of 100℃, and a reaction time of 24h. After the hydrothermal reaction is completed, let the autoclave cool to room temperature and dry the reaction product in an oven at 60℃. Then calcine it in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0162] The "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0163] The catalyst in this example was prepared according to the method in Example 1.
[0164] Comparative Example 2
[0165] This example of titanium-modified mesoporous alumina is the same as in Example 1.
[0166] The preparation method of the impregnation solution containing the second active metal in this example includes:
[0167] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:7.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water is 5:15:8:85. The mass ratio of oil phase to internal aqueous phase is 1.0:0.6. The mass ratio of nickel source (calculated as nickel oxide):hydrophilic agent:water is 18:32:325. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 0.7:1.0.
[0168] (a) Molybdenum oxide and phosphoric acid were added to deionized water in sequence. A reflux condenser was used during the reaction. The reaction started at 28°C. During the reaction, the stirring speed was 500 r / min. When the temperature was raised to 120°C, it was maintained for 3 hours. A constant stirring speed was maintained until a transparent and clear solution was obtained, thus obtaining the internal aqueous phase.
[0169] (b) Add basic nickel carbonate and a hydrophilic agent to water to obtain an external aqueous phase;
[0170] (c) The surfactant glyceryl monostearate, silicone oil, and co-emulsifier were added to the aqueous phase obtained in step (a) while stirring. The shear homogenization rate was 15,000 rpm, the shear homogenization time was 4 min, and the temperature during the shear homogenization process was 75°C. After the droplets were dispersed into an emulsion, an "aqueous / oil phase" type emulsion was obtained.
[0171] (d) Add the “inner aqueous phase / oil phase” emulsion obtained in step (c) to the outer aqueous phase obtained in step (2) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” impregnation solution.
[0172] The preparation of the hydrogenation catalyst in this example is the same as in Example 1.
[0173] Compared with Example 1, the hydrogenation catalyst obtained by impregnating the supported catalyst intermediate with an "inner aqueous phase / oil phase / outer aqueous phase" impregnation liquid prepared by the method of Comparative Example 2 could not meet the requirements of long-term operation of the hydrogenation test device, and the relative demetallization rate was only 93.18% after 2000 hours of operation.
[0174] Comparative Example 3
[0175] The preparation of titanium-modified mesoporous alumina in this example is the same as in Example 1.
[0176] The preparation of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0177] Preparation of the catalyst in this example:
[0178] (1) 352g of titanium-modified mesoporous alumina, 7.5g of guar gum powder, 73g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier.
[0179] (2) Prepare an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, saturate the composite carrier obtained in step (1), and after drying at 120℃ for 6 hours and calcining at 550℃ for 4 hours, obtain the residue oil demetallization catalyst.
[0180] Comparative Example 4
[0181] The preparation of titanium-modified mesoporous alumina in this example is the same as in Example 1.
[0182] In the preparation process of the catalyst in this example, step (2) uses a conventional Mo-Ni-P impregnation solution to impregnate the supported catalyst intermediate, wherein the molybdenum, nickel and phosphorus content in the impregnation solution is the same as that in the impregnation solution of Example 1.
[0183] (1) 268g of titanium-modified mesoporous alumina, 84g of high-temperature activated carbon (heat resistance temperature of 900℃, pore volume of 1.7mL / g, and pore volume of 50~300nm accounting for 40% of the total pore volume), 7.5g of guar gum powder, 73g of ammonium heptamolybdate and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0184] (2) Prepare a Mo-Ni-P impregnation solution by taking molybdenum oxide, basic nickel carbonate, phosphoric acid and deionized water, saturate the composite support obtained in step (1), dry at 120℃ for 6h and calcine at 550℃ for 4h to obtain the residue oil demetallization catalyst.
[0185] Comparative Example 5
[0186] The preparation of titanium-modified mesoporous alumina in this example is the same as in Example 1.
[0187] In the preparation process of the catalyst in this example, the active metal molybdenum is not introduced in step (1). The mass of MoO3 introduced into the catalyst by the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal in step (2) is 100% of the total MoO3 loading in the catalyst.
[0188] (1) 268g of titanium-modified mesoporous alumina, 84g of high-temperature activated carbon (heat resistance temperature of 900℃, pore volume of 1.7mL / g, and pore volume of 50~300nm accounting for 40% of the total pore volume), 7.5g of guar gum powder and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 650℃ for 4h to obtain a composite carrier;
[0189] (2) Prepare an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, saturate the composite carrier obtained in step (1), and after drying at 120℃ for 6 hours and calcining at 550℃ for 4 hours, obtain the residue oil demetallization catalyst.
[0190] Table 1 shows the properties of the titanium-modified mesoporous alumina obtained in each example.
[0191]
[0192] Table 2 shows the composition of the catalysts obtained in each example.
[0193]
[0194] Table 3 Properties of the catalysts obtained in each example
[0195]
[0196]
[0197] Evaluation test
[0198] Activity stability tests were conducted on Examples 1-5 and Comparative Examples 1-5 using a 200mL fixed-bed hydrogenation test apparatus. The feedstock was residue oil with a density of 989.7 kg / m³. 3 (20℃), S content 2.64wt%, Ni and V contents 27.5μg / g and 57.7μg / g respectively, CCR content 11.4wt%, the demetallization rate after 2000h of operation in Example 1 was 100%, and all others are relative demetallization rates. Specific experimental conditions are shown in Table 4, and experimental results are shown in Tables 5 and 6.
[0199] Table 4 Test Conditions
[0200] Reaction temperature, °C 375 Reaction pressure, MPa 15.7 <![CDATA[Liquid hourly volume space velocity, h -1 > 1.5 Hydrogen-to-oil ratio, V / V 700
[0201] Table 5. Test results of the hydrogenation demetallization catalysts in each example.
[0202] Example 1 Example 2 Example 3 Example 4 Example 5 Relative demetallization rate, % 100 98.37 98.54 96.79 96.24
[0203] Table 6. Experimental results of hydrogenation demetallization catalysts in each comparative example.
[0204] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Relative demetallization rate, % 93.51 93.18 93.68 92.87 93.28
[0205] The specific embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for preparing a hydrogenation catalyst, comprising the following steps: (1) Titanium-modified mesoporous alumina, activated carbon, a first active metal source and molding aid are mixed and shaped, dried and calcined to obtain a composite carrier containing the first active metal. (2) The second active metal is loaded onto the composite support obtained in step (1), dried, and calcined to obtain the catalyst.
2. The preparation method according to claim 1, characterized in that, In step (1), the activated carbon is a high-temperature activated carbon with a minimum heat resistance temperature of not less than 700°C, preferably 750-900°C; And / or, the activated carbon has a pore volume of 1.0 to 1.8 mL / g, and the pore volume with a pore size of 50.0 to 300.0 nm accounts for 15% to 45% of the total pore volume.
3. The preparation method according to claim 1, characterized in that, In step (1), the molding aid is one or more of guar gum powder and methylcellulose; Preferably, the mass of the molding aid added is 1.0% to 8.0% of the sum of the mass of mesoporous alumina and activated carbon.
4. The preparation method according to claim 1, characterized in that, In step (1), the first active metal is one or more of the group VIB metals, preferably Mo and / or W; And / or, in step (1), the mass of the first active metal source, in terms of oxides, is 10% to 25% of the total mass of mesoporous alumina and activated carbon.
5. The preparation method according to claim 1, characterized in that, In step (1), the calcination temperature is 500-650℃ and the calcination time is 3-8h; And / or, in step (2), the calcination temperature is 500-650°C and the calcination time is 3-8h.
6. The preparation method according to claim 1, characterized in that, In step (2), the second active metal includes Group VIB metals and Group VIII metals; preferably, the second active metal is introduced into the catalyst through an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal.
7. The preparation method according to claim 6, characterized in that, The "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing a second active metal includes an inner aqueous phase, an oil phase coating the inner aqueous phase, and an outer aqueous phase; wherein, the inner aqueous phase includes a Group VIB metal source, a co-emulsifier, a water-soluble polymer, water, and an optional auxiliary agent source, the outer aqueous phase includes a Group VIII metal source, a hydrophilic agent, and water; and the oil phase includes a surfactant and oil.
8. The preparation method according to claim 7, characterized in that, The mass ratio of surfactant to oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0; And / or, the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0; And / or, the mass ratio of the "internal aqueous phase / oil phase" to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.
0.
9. The preparation method according to claim 7, characterized in that, The co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, and glycerin; And / or, the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate; And / or, the Group VIB metal is Mo and / or W, and the Group VIII metal is Ni and / or Co; And / or, the additive is selected from at least one of phosphorus, silicon or boron, preferably phosphorus; And / or, the hydrophilic agent is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide; And / or, the surfactant is selected from one or more of glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol; And / or, the oil is selected from at least one of silicone oil and vegetable oil, the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
10. The preparation method according to claim 7, characterized in that, In the internal aqueous phase, the mass concentration of water-soluble polymer is 4.0% to 14.0%; And / or, in the internal aqueous phase, the mass concentration of the co-emulsifier is 0.5% to 5.0%; And / or, in the internal aqueous phase, the concentration of the additive, calculated as oxide, is 0–12.0 g / 100 mL, preferably 0.5–12.0 g / 100 mL; And / or, in the internal aqueous phase, the concentration of Group VIB metals as oxides is 8-80 g / 100 mL, preferably 10-60 g / 100 mL; And / or, in the external aqueous phase, the concentration of Group VIII metals as oxides is 2 to 50 g / 100 mL, preferably 5 to 30 g / 100 mL; And / or, in the external aqueous phase, the mass concentration of the hydrophilic agent is 5.0% to 15.0%.
11. The preparation method according to claim 7, characterized in that, The method for preparing the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal includes: (a) The surfactant and oil are mixed and heated to obtain the oil phase; (b) Mix the co-emulsifier, the Group VIB metal source, water and optional auxiliary source, and heat to obtain a clear solution; (c) Add a water-soluble polymer to the clear solution obtained in step (b) to obtain an internal aqueous phase; (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a) while the oil phase remains liquid during the dropwise addition. Simultaneously, stirring and shearing are performed to homogenize the mixture, resulting in an "aqueous phase / oil phase" emulsion. (e) Mixing a Group VIII metal source with water containing a hydrophilic agent to obtain an external aqueous phase; (f) The "inner aqueous phase / oil phase" type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (e) to obtain an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution.
12. The preparation method according to claim 11, characterized in that, In step (a), the heating temperature is 45–85°C; And / or, in step (b), the heating to a temperature of 90–120°C; And / or, in step (d), the stirring-shear homogenization process is carried out at a stirring speed of 10,000 to 18,000 rpm, a homogenization time of 3 to 8 min, and a homogenization temperature of 50 to 85°C.
13. The preparation method according to claim 1, characterized in that, In step (1), the molar ratio of titanium to aluminum in the titanium-modified mesoporous alumina is 0.2 to 1.
0. And / or, in the titanium-modified alumina, the amount of medium-strong acid accounts for 59% to 65% of the total acid content, preferably 62% to 65%.
14. The preparation method according to claim 1, characterized in that, In step (1), the specific surface area of the titanium-modified mesoporous alumina is 300–450 m². 2 / g, preferably 335-450m 2 / g, with a mesopore size of 11.0–25.0 nm, preferably 13.0–17.0 nm, and a pore volume of 1.10–1.50 mL / g, preferably 1.25–1.50 mL / g.
15. The preparation method according to claim 1, characterized in that, In step (1), the method for preparing the titanium-modified mesoporous alumina includes: (I) Mix aluminum source, acid and alcohol, and perform pre-hydrolysis to obtain solution A; (II) Mix the template agent and alcohol to obtain solution B; (III) Mix solution A, solution B and the solution containing titanium source to obtain solution D; (IV) After adding the bifunctional structure directing agent dropwise to solution D, perform hydrothermal treatment, dry, and calcine to obtain the titanium-modified mesoporous alumina.
16. The preparation method according to claim 15, characterized in that, In step (I), the temperature of the pre-hydrolysis is 20–60°C, and the time of the pre-hydrolysis is 1–12 h; And / or, in step (I), the ethanol / aluminum molar ratio is 10.0 to 80.0, preferably 15.0 to 55.0; And / or, in step (I), the acid / aluminum molar ratio is 1.0 to 10.0, preferably 1.0 to 7.
0.
17. The preparation method according to claim 15, characterized in that, In step (I), the aluminum source is one or more of aluminum nitrate, aluminum chloride, and aluminum isopropoxide; the acid is one or more of nitric acid, sulfuric acid, and hydrochloric acid; and the alcohol is one or more of ethanol, propanol, and butanol.
18. The preparation method according to claim 15, characterized in that, In step (II), the template agent is at least one of P123, SDBS and AOT, preferably P123; And / or, in step (II), the alcohol is one or more of ethanol, propanol, and butanol.
19. The preparation method according to claim 15, characterized in that, In step (I), the aluminum source, acid and alcohol are first mixed and pre-hydrolyzed to obtain a precursor solution. Then, an ionic emulsifier is added dropwise to the precursor solution to obtain solution A. And / or, the ionic emulsifier is one or more of sodium dodecyl sulfate and fatty polyoxyethylene ether sulfate salt; preferably, the amount of the ionic emulsifier added is related to the amount of the precursor solution by 5 to 20 g / 100 mL.
20. The preparation method according to claim 15, characterized in that, The molar ratio of the sum of the aluminum source in step (I) and the titanium source in step (III) to the template agent in step (II) is 50 to 90. And / or, in step (II), the molar ratio of alcohol to template agent is 300 to 1000.
21. The preparation method according to claim 15, characterized in that, In step (IIII), the titanium source-containing solution includes a titanium source, an acid, and an alcohol, wherein the alcohol is preferably ethanol, the acid is preferably nitric acid, and the titanium source is selected from at least one of titanium isopropoxide, tetrabutyl titanate, methyl titanate, and tetraethyl titanate. And / or, in the titanium source-containing solution, the volume ratio of alcohol to acid is 4 to 12; And / or, in the titanium-containing solution, the ratio of the mass of titanium to the sum of the volumes of acid and alcohol is 0.02 to 0.15 g / mL; And / or, the molar ratio of the titanium source to the aluminum source in step (I) is 0.2 to 0.
8.
22. The preparation method according to claim 15, characterized in that, In step (IV), the bifunctional directing agent is polyethylene glycol-distearatephosphatidylethanolamine; Preferably, the molar ratio of the bifunctional structure directing agent to the sum of the bifunctional structure directing agent and the aluminum source in solution A is 0.05 to 0.
35.
23. The preparation method according to claim 15, characterized in that, In step (IV), the conditions for the hydrothermal treatment are: temperature 140-240℃, preferably 150-235℃, and time 3-10h, preferably 4-8h; And / or, in step (IV), the calcination temperature is 500–650°C and the calcination time is 3–8 h.
24. The hydrogenation catalyst obtained by any of the preparation methods described in claims 1-23.
25. The hydrogenation catalyst according to claim 24, characterized in that, The hydrogenation catalyst includes a composite support containing a first active metal and a second active metal. The composite support containing the first active metal includes titanium-modified mesoporous alumina, activated carbon, and the first active metal. Preferably, the first active metal is selected from at least one of Group VIB metals, preferably Mo and / or W; the second active metal includes at least one of Group VIII metals and at least one of Group VIB metals, preferably Ni and / or Co of Group VIII metals, and preferably Mo and / or W of Group VIB metals.
26. The hydrogenation catalyst according to claim 25, characterized in that, In the composite carrier, the mass ratio of titanium-modified mesoporous alumina to activated carbon is 2.5 to 6.
5.
27. The hydrogenation catalyst according to claim 25, characterized in that, In the catalyst, based on the mass of the catalyst, the content of Group VIB metal oxide is 6% to 20%, preferably 10% to 18%, and the content of Group VIII metal oxide is 1% to 10%, preferably 2% to 8%; wherein the mass ratio of Group VIB metal oxide in the first active metal to Group VIB metal oxide in the second active metal is 0.5 to 6.
0. Preferably, the catalyst includes an additive, and the additive content, calculated as oxide, is 0-8% based on the mass of the catalyst, preferably 1-6%.
28. The hydrogenation catalyst according to claim 25, characterized in that, In the catalyst, mesopores with a pore size of 6.0–25.0 nm account for 20.0%–45.0% of the total pore volume, preferably 30.0%–41.0%, and macropores with a pore size of 50.0–300.0 nm account for 20.0%–35.0% of the total pore volume, preferably 23.5%–35.0%.
29. The hydrogenation catalyst according to claim 25, characterized in that, In the catalyst, the molar ratio of the amount of Brønsted acid to the sum of the amounts of Brønsted acid and L-acid is 0.310 to 0.390, preferably 0.350 to 0.
388.
30. The application of the hydrogenation catalyst according to any one of claims 1-23 or the hydrogenation catalyst prepared by any one of claims 24-29 in the hydrodemetallization of residue oil.
Citation Information
Patent Citations
Highly thermostable and ordered mesoporous alumina material and preparation method thereof
CN103539173A
